F. Scott Fitzgerald and Zelda Sayre Fitzgerald: Plagiarism, Destructive Ambition, and “Imposter Syndrome”? - Nash, Ph.D., Susan Smith (IJRDO - Journal of Social Science and Humanities Research, 2021)
Before she was committed to a psychiatric hospital for her self-destructive and erratic behavior, Zelda Sayre Fitzgerald, had been accused by her husband, the highly successful F. Scott Fitzgerald, of plagiarizing his work. She accused him of the same thing. And yet, there is a body of evidence that demonstrates that passages of F. Scott’s writing were derived from her journals and letters, and that the work that was published under both their names as co-authors was actually exclusively her work. There was even one short story that was published under his name, but in reality, completely written by Zelda. The relationship that they had with each other, with their work, and the world at large gives rise to a number of interesting phenomena when two ambitious writers are in a relationship, the first of which is rivalry, followed by existential (or ontological) insecurity, protracted writer’s block,  and even the emergence of “imposter syndrome.” This paper reports the results of a close investigation of their history, their writing, and illuminating psychological and philosophical phenomena. It also contextualizes their central themes within literary Modernism and the “Lost Generation,” writing and influencing each other in the 1920s.